5.3.2 Problems 101 to 200

Table 5.287: Second order ode

#

ODE

Mathematica

Maple

346

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = x \left ({\mathrm e}^{-x}-{\mathrm e}^{-2 x}\right ) \]

347

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = x \,{\mathrm e}^{3 x} \sin \left (3 x \right ) \]

351

\[ {}y^{\prime \prime }+4 y = 2 x \]

352

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{x} \]

353

\[ {}y^{\prime \prime }+9 y = \sin \left (2 x \right ) \]

354

\[ {}y^{\prime \prime }+y = \cos \left (x \right ) \]

355

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 1+x \]

358

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \sin \left (3 x \right ) \]

363

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \sin \left (3 x \right ) \]

364

\[ {}y^{\prime \prime }+9 y = \sin \left (x \right )^{4} \]

365

\[ {}y^{\prime \prime }+y = x \cos \left (x \right )^{3} \]

366

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 4 \,{\mathrm e}^{x} \]

367

\[ {}y^{\prime \prime }-2 y^{\prime }-8 y = 3 \,{\mathrm e}^{-2 x} \]

368

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 2 \,{\mathrm e}^{2 x} \]

369

\[ {}y^{\prime \prime }-4 y = \sinh \left (2 x \right ) \]

370

\[ {}y^{\prime \prime }+4 y = \cos \left (3 x \right ) \]

371

\[ {}y^{\prime \prime }+9 y = \sin \left (3 x \right ) \]

372

\[ {}y^{\prime \prime }+9 y = 2 \sec \left (3 x \right ) \]

373

\[ {}y^{\prime \prime }+y = \csc \left (x \right )^{2} \]

374

\[ {}y^{\prime \prime }+4 y = \sin \left (x \right )^{2} \]

375

\[ {}y^{\prime \prime }-4 y = x \,{\mathrm e}^{x} \]

376

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 72 x^{5} \]

377

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x^{3} \]

378

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = x^{4} \]

379

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+3 y = 8 x^{{4}/{3}} \]

380

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = \ln \left (x \right ) \]

381

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = x^{2}-1 \]

382

\[ {}y^{\prime \prime }+y = 2 \sin \left (x \right ) \]

383

\[ {}x^{\prime \prime }+9 x = 10 \cos \left (2 t \right ) \]

384

\[ {}x^{\prime \prime }+4 x = 5 \sin \left (3 t \right ) \]

385

\[ {}x^{\prime \prime }+100 x = 225 \cos \left (5 t \right )+300 \sin \left (5 t \right ) \]

386

\[ {}x^{\prime \prime }+25 x = 90 \cos \left (4 t \right ) \]

387

\[ {}m x^{\prime \prime }+k x = F_{0} \cos \left (\omega t \right ) \]

388

\[ {}x^{\prime \prime }+4 x^{\prime }+4 x = 10 \cos \left (3 t \right ) \]

389

\[ {}x^{\prime \prime }+3 x^{\prime }+5 x = -4 \cos \left (5 t \right ) \]

390

\[ {}2 x^{\prime \prime }+2 x^{\prime }+x = 3 \sin \left (10 t \right ) \]

391

\[ {}x^{\prime \prime }+3 x^{\prime }+3 x = 8 \cos \left (10 t \right )+6 \sin \left (10 t \right ) \]

392

\[ {}x^{\prime \prime }+4 x^{\prime }+5 x = 10 \cos \left (3 t \right ) \]

393

\[ {}x^{\prime \prime }+6 x^{\prime }+13 x = 10 \sin \left (5 t \right ) \]

394

\[ {}x^{\prime \prime }+2 x^{\prime }+26 x = 600 \cos \left (10 t \right ) \]

395

\[ {}x^{\prime \prime }+8 x^{\prime }+25 x = 200 \cos \left (t \right )+520 \sin \left (t \right ) \]

396

\[ {}x^{\prime \prime }+2 x^{\prime }+2 x = 2 \cos \left (\omega t \right ) \]

397

\[ {}x^{\prime \prime }+4 x^{\prime }+5 x = 10 \cos \left (\omega t \right ) \]

398

\[ {}x^{\prime \prime }+6 x^{\prime }+45 x = 50 \cos \left (\omega t \right ) \]

399

\[ {}x^{\prime \prime }+10 x^{\prime }+650 x = 100 \cos \left (\omega t \right ) \]

514

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

515

\[ {}x y^{\prime \prime }+3 y^{\prime }+x y = 0 \]

516

\[ {}x y^{\prime \prime }-y^{\prime }+36 x^{3} y = 0 \]

517

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+\left (x +8\right ) y = 0 \]

518

\[ {}36 x^{2} y^{\prime \prime }+60 x y^{\prime }+\left (9 x^{3}-5\right ) y = 0 \]

519

\[ {}16 x^{2} y^{\prime \prime }+24 x y^{\prime }+\left (144 x^{3}+1\right ) y = 0 \]

520

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

521

\[ {}4 x^{2} y^{\prime \prime }-12 x y^{\prime }+\left (15+16 x \right ) y = 0 \]

522

\[ {}16 x^{2} y^{\prime \prime }-\left (-144 x^{3}+5\right ) y = 0 \]

523

\[ {}2 x^{2} y^{\prime \prime }-3 x y^{\prime }-2 \left (-x^{5}+14\right ) y = 0 \]

524

\[ {}y^{\prime \prime }+x^{4} y = 0 \]

525

\[ {}x y^{\prime \prime }+4 x^{3} y = 0 \]

526

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

530

\[ {}x^{\prime \prime }+4 x = 0 \]

531

\[ {}x^{\prime \prime }+9 x = 0 \]

532

\[ {}x^{\prime \prime }-x^{\prime }-2 x = 0 \]

533

\[ {}x^{\prime \prime }+8 x^{\prime }+15 x = 0 \]

534

\[ {}x^{\prime \prime }+x = \sin \left (2 t \right ) \]

535

\[ {}x^{\prime \prime }+4 x = \cos \left (t \right ) \]

536

\[ {}x^{\prime \prime }+x = \cos \left (3 t \right ) \]

537

\[ {}x^{\prime \prime }+9 x = 1 \]

538

\[ {}x^{\prime \prime }+4 x^{\prime }+3 x = 1 \]

539

\[ {}x^{\prime \prime }+3 x^{\prime }+2 x = t \]

541

\[ {}x^{\prime \prime }+6 x^{\prime }+25 x = 0 \]

542

\[ {}x^{\prime \prime }-6 x^{\prime }+8 x = 2 \]

543

\[ {}x^{\prime \prime }-4 x = 3 t \]

544

\[ {}x^{\prime \prime }+4 x^{\prime }+8 x = {\mathrm e}^{-t} \]

551

\[ {}x^{\prime \prime }+4 x^{\prime }+13 x = t \,{\mathrm e}^{-t} \]

552

\[ {}x^{\prime \prime }+6 x^{\prime }+18 x = \cos \left (2 t \right ) \]

553

\[ {}x^{\prime \prime }+9 x = 6 \cos \left (3 t \right ) \]

554

\[ {}x^{\prime \prime }+\frac {2 x^{\prime }}{5}+\frac {226 x}{25} = 6 \,{\mathrm e}^{-\frac {t}{5}} \cos \left (3 t \right ) \]

555

\[ {}t x^{\prime \prime }+\left (t -2\right ) x^{\prime }+x = 0 \]

556

\[ {}t x^{\prime \prime }+\left (3 t -1\right ) x^{\prime }+3 x = 0 \]

557

\[ {}t x^{\prime \prime }-\left (4 t +1\right ) x^{\prime }+2 \left (2 t +1\right ) x = 0 \]

558

\[ {}t x^{\prime \prime }+2 \left (t -1\right ) x^{\prime }-2 x = 0 \]

559

\[ {}t x^{\prime \prime }-2 x^{\prime }+t x = 0 \]

560

\[ {}t x^{\prime \prime }+\left (4 t -2\right ) x^{\prime }+\left (13 t -4\right ) x = 0 \]

561

\[ {}x^{\prime \prime }+4 x = f \left (t \right ) \]

562

\[ {}x^{\prime \prime }+2 x^{\prime }+x = f \left (t \right ) \]

563

\[ {}x^{\prime \prime }+4 x^{\prime }+13 x = f \left (t \right ) \]

564

\[ {}x^{\prime \prime }+4 x = \delta \left (t \right ) \]

565

\[ {}x^{\prime \prime }+4 x = \delta \left (t \right )+\delta \left (t -\pi \right ) \]

566

\[ {}x^{\prime \prime }+4 x^{\prime }+4 x = 1+\delta \left (t -2\right ) \]

567

\[ {}x^{\prime \prime }+2 x^{\prime }+x = t +\delta \left (t \right ) \]

568

\[ {}x^{\prime \prime }+2 x^{\prime }+2 x = 2 \delta \left (t -\pi \right ) \]

569

\[ {}x^{\prime \prime }+9 x = \delta \left (t -3 \pi \right )+\cos \left (3 t \right ) \]

570

\[ {}x^{\prime \prime }+4 x^{\prime }+5 x = \delta \left (t -\pi \right )+\delta \left (t -2 \pi \right ) \]

571

\[ {}x^{\prime \prime }+2 x^{\prime }+x = \delta \left (t \right )-\delta \left (t -2\right ) \]

572

\[ {}x^{\prime \prime }+4 x = f \left (t \right ) \]

573

\[ {}x^{\prime \prime }+6 x^{\prime }+9 x = f \left (t \right ) \]

574

\[ {}x^{\prime \prime }+6 x^{\prime }+8 x = f \left (t \right ) \]

575

\[ {}x^{\prime \prime }+4 x^{\prime }+8 x = f \left (t \right ) \]

807

\[ {}y^{\prime \prime }-y = 0 \]

808

\[ {}y^{\prime \prime }-9 y = 0 \]

809

\[ {}y^{\prime \prime }+4 y = 0 \]